Perceptions of Students toward Learning-Oriented Assessment: The Potential of Peer Assessment - Toledo, Sandra Vázquez; Latorre-Cosculluela, Cecilia; González-Yubero, Sara; Mairal-Llebot, María (International Journal of Learning, Teaching and Educational Research, 2025)
This study used a mixed approach to examine the implications and benefits of intergroup peer assessment in the context of cooperative work in higher education. The main objective was to analyze how this assessment strategy influenced learning, motivation, and the development of transversal competences of a sample of 305 students who were enrolled for a degree in primary education at the University of Zaragoza. An ad hoc questionnaire was used to collect quantitative and qualitative data on students’ perceptions of their engagement with the task, the relationship between peer assessment and their learning, and the improvement of their competences, such as active listening, constructive criticism, and critical judgment. Firstly, quantitative and descriptive analyses were carried out. A Cronbach’s alpha reliability analysis was also carried out. Secondly, in order to structure the qualitative information, a category tree was developed. The main results show that students value peer assessment positively because it facilitates their active learning, improves group cohesion, and fosters the development of key competences. In addition, the researchers observed an increase in motivation, ability to work in a team and critical reflection on the results and processes of students’ own work. These findings suggest that intergroup peer assessment not only supports knowledge acquisition, but also promotes cooperation between and engagement and critical thinking by students. In conclusion, intergroup peer assessment emerges as a powerful tool to enhance learning and competence development in higher education by proposing a more participatory and formative approach to assessment processes. https://doi.org/10.26803/ijlter.24.2.16